CO2 Stripping from Monoethanolamine through a Polypropylene/CH3SiO2 Composite Hollow‐Fiber Membrane Contactor. Issue 8 (14th July 2022) - Amirabedi, Parya; Akbari, Ali; Yegani, Reza; Raveshiyan, Saba
Abstract: To remove CO2 through a membrane contactor system, composite polypropylene (PP) hollow‐fiber membranes were fabricated by dispersing methyl‐grafted silica nanoparticles in a PP membrane matrix. A set of characterization tests including FTIR spectroscopy, FESEM, AFM, TEM, porosity, contact angle, mechanical strength, and CO2 stripping experiments was carried out. The results showed that the porosity, hydrophobicity, roughness, and CO2 stripping flux of the composite membranes increased with increasing content of inorganic NPs. At an absorbent flow rate of 2.5 m s −1, the CO2 stripping flux of composite membranes containing 1.5 wt % NPs was higher than those of most other hydrophobic membrane contactors. Abstract : Stripping CO2 from an absorbent is a crucial step in CO2 removal, which is an essential process in many industrial areas. Hollow‐fiber membranes were fabricated by dispersing methyl‐grafted silica nanoparticles in a polypropylene matrix and used for CO2 stripping in a membrane contactor, the stripping performance of which surpassed those of most other hydrophobic membrane contactors.